Enhancing Maqasid Syariah through E-Banking: A Qualitative Analysis of Syariah-Compliant Financial Transactions: Meningkatkan Maqasid Syariah melalui E-Banking: Analisis Kualitatif atas Transaksi Keuangan yang Sesuai Syariah - Masruchin, Masruchin; Wicaksono, Arief; Silvia, Nur Manna; Dimawan, Amelia Eka (Indonesian Journal of Law and Economics Review, 2023)
The article presents a qualitative study analyzing the utilization of e-banking syariah from the perspective of Maqasid Syariah, focusing on Islamic principles in financial transactions. Employing a descriptive approach and content analysis, data were collected through literature review, documentation, and interviews. The findings reveal that e-banking syariah significantly contributes to achieving Maqasid Syariah, promoting responsible financial practices aligned with Islamic principles. The study highlights benefits such as ethical transactions, wise financial decisions, and improved investment management. The implications emphasize the relevance of these findings for professionals and scholars in the field of Islamic finance and banking. Highlight: Significance of E-Banking Syariah: The research highlights the substantial benefits of utilizing e-banking syariah in achieving Maqasid Syariah, including adherence to Islamic principles in financial transactions and wise financial decision-making. Holistic Well-Being: E-Banking Syariah contributes to the preservation of individuals' well-being in aspects of religion, soul, intellect, lineage, and wealth, promoting a balanced and spiritually fulfilling life. Responsible Implementation: The study emphasizes the importance of grounding the use of e-banking syariah on strong Islamic principles, promoting transparency, and accountability in financial management while avoiding prohibited practices. Keyword: E-Banking Syariah, Maqasid Syariah, Islamic Finance, Financial Transactions, Qualitative Study